60=512⋅(Wn)

Rewrite the equation as 512⋅(Wn)=60.

512⋅(Wn)=60

Multiply both sides of the equation by 125.

125⋅512⋅(Wn)=125⋅60

Simplify 125⋅512⋅(Wn).

Cancel the common factor of 12.

Cancel the common factor.

125⋅512⋅(Wn)=125⋅60

Rewrite the expression.

15⋅5⋅(Wn)=125⋅60

15⋅5⋅(Wn)=125⋅60

Cancel the common factor of 5.

Cancel the common factor.

15⋅5⋅(Wn)=125⋅60

Rewrite the expression.

1⋅(Wn)=125⋅60

1⋅(Wn)=125⋅60

Multiply Wn by 1.

Wn=125⋅60

Wn=125⋅60

Simplify 125⋅60.

Cancel the common factor of 5.

Factor 5 out of 60.

Wn=125⋅(5(12))

Cancel the common factor.

Wn=125⋅(5⋅12)

Rewrite the expression.

Wn=12⋅12

Wn=12⋅12

Multiply 12 by 12.

Wn=144

Wn=144

Wn=144

Divide each term in Wn=144 by n.

Wnn=144n

Cancel the common factor of n.

Cancel the common factor.

Wnn=144n

Divide W by 1.

W=144n

W=144n

W=144n

Solve for W 60=5/12*(Wn)